A cyclic peptide retards the proliferation of DU145 prostate cancer cells in vitro and in vivo through inhibition of FGFR2. Issue 3 (14th December 2020) - Zhang, Yibo; Ouyang, Man; Wang, Hailong; Zhang, Bihui; Guang, Wenhua; Liu, Ruiwu; Li, Xiaocen; Shih, Tsung‐Chieh; Li, Zhixin; Cao, Jieqiong; Meng, Qiling; Su, Zijian; et al.
Abstract: In malignancies, fibroblast growth factor receptors (FGFRs) signaling is reinforced through overexpression of fibroblast growth factors (FGFs) or their receptors. FGFR2 has been proposed as a target for cancer therapy, because both the expression and activation of FGFR2 are boosted in various malignant carcinomas. Although several chemicals have been designed against FGFR2, they did not exhibit enough specificity and might bring potential accumulated toxicity. In this study, we developed an epitope peptide (P5) and its cyclic derivative (DcP5) based on the structure of FGF2 to limit the activation of FGFR2. The anticancer activities of P5 and DcP5 were examined in vitro and in vivo. Our results demonstrated that P5 significantly inhibited the cell proliferation in FGFR2‐dependent manner in DU145 cells and retarded tumor growth in DU145 xenograft model with negligible toxicity toward normal organs. Further investigations found that the Gln4 and Glu6 residues of P5 bind to FGFR2 to abolish its activation. Moreover, we developed the P5 cyclic derivative, DcP5, which achieved reinforced stability and anticancer activity in vivo. Our findings suggest P5 and its cyclic derivative DcP5 as potential candidates for anticancer therapy. Abstract : In various malignancies, fibroblast growth factor receptors (FGFRs) signaling is reinforced, resulting in tumor progression and poor prognosis. Herein, we developed an FGFR2 competitive inhibitory peptide (P5) to limit the overactivation of FGFR2 signaling. Moreover, this P5 peptide was upgraded to DcP5 through cyclization to achieve improved in vivo stability and FGFR2‐binding affinity.